(untitled) (Baghdad Science Journal, 2013)
Inflammasome is a multiprotein oligomer complex which is the precursor procaspase-1 and is a component of the innate immune system so that this study aimed to determine the serum levels of interleukin-1? and 18 in patients with T2D and simple obesity in an attempt to clarify the role of inflammasome in these disorders.Twenty five known cases of T2D, twenty four patients with simple obesity and twenty healthy subjects were randomly recruited from AL-Kindy Teaching Hospital in Baghdad to enroll in this study. All the data about the demographic characteristics and anthropometric measurements were determined in all patients, also the C-reactive protein and serum interleukin (IL)-1? and IL-18 levels were obtained from each patient. The results showed that patients who had positive C-reactive protein (? 6 mg/L) had significant high level of serum 1? and IL-18 levels. Concomitant significant increase in serum levels of IL-1? and IL-18 was observed only in 8% (2 out of 25) of T2D. It concludes that the activity of inflammasome is observed in low percent of T2D and this activity does not related to the obesity.